Local dynamics of DDE with large delay in the vicinity of the self-similar cycle - D. V. Glazkov; S. A. Kaschenko (Моделирование и анализ информационных систем, 2010)
We research the local dynamics of a complex differential equation with large delay in the vicinity of the self-similar cycle. The quasinormal forms method is used for a problem analysis.